GSM based espec oven automatic control: article / Mohd Zul Azman Abdullah - Abdullah, Mohd Zul Azman (2013)
This project presents an automatic control damper for "Espec Oven" which is widely used in the LED manufacturing plant. Espec Oven is used to cure LED autofocus. The purpose of this project is to design an automatic damper controller and send acknowledge via SMS to the operator. This project consists of several main parts based on Espec Oven in the factory manufacturer of small electronic components. The parts include a timer circuit to set maximum 4 hours to operate up to 135°C, a SIEMENS TC35 GSM Module to send SMS or call the operator when the damper lift up automatically, and DC geared motor with encoder to lift up the damper after sufficient time 4 hours. This project able to facilitate the work of the operator in charge of the oven. By this project also, avoid finish product from the damage or over heat due to human error.